Effects of gadolinium and gadolinium chelates on intracellular calcium signaling in sensory neurons - Baykara, Murat; Ozcan, Mete; Bilgen, Mehmet; Kelestimur, Haluk (Elsevier Ireland Ltd, 2019)
Magnetic resonance imaging (MRI) employs gadolinium chelates as contrast agents to provide signal enhancement in radiological images. However, the instability of the chelates presents a challenge as the released gadolinium ion (Gd3+) from the chelates becomes toxic to the surrounding biological tissue. Chelates such as gadodiamide, gadoterate meglumine, gadobutrol and gadobenate dimeglumine are common contrast agents used in clinics. The release of Gd3+ from these agents have been reported previously using experimental setups involving water, but this study evaluates the release in cell culture of dorsal root ganglion (DRG) neurons as this model system is relevant to neuronal toxicity induced by these agents. DRG neurons were grown in primary culture following enzymatic and mechanical dissociation of ganglia from a 2-day-old neonatal Wistar rat. Using Fura-2 based calcium imaging, the effects of gadolinium chelates on free intracellular Ca2+ transport was assessed. The findings indicated that the contrast agent gadoterate meglumine exhibited the best performance in complex stability, independent of its concentration, and thus it must be taken into consideration in standard MRI exams and neuroimaging. The free Gd3+ released from the other agents is also of great concern as it may impact the neurophysiology of the neuronal cells in general, even in normal patients without nephrogenic systemic fibrosis.
Keywords: Optical imaging; Gadolinium; Contrast media; Calcium signaling; Sensory neurons